Analisis Pembangunan Kepemudaan di Kota Banjarbaru menggunakan Pendekatan Indeks Pembangunan Pemuda (Domain Pendidikan dan Lapangan & Kesempatan Kerja) - Siska Fitriyanti; Herry Azhar Pradana (Jurnal Kebijakan Pembangunan, 2022)
The Youth Development Index (YDI) is an instrument to measure youth development in a region. Youth development is a vital need to prepare quality people for future development. In Indonesia, YDI is only available at the provincial level. However, district and city governments are obliged to apply youth development in regional development planning to support the achievement of provincial YDI. This paper aims to analyze youth development in the education and employment sector in Banjarbaru City based on YDI indicators in these domains: MYS, SM-APK, APK-PT, white-collar entrepreneur, and youth unemployment rate. This study used a qualitative approach and analyzed descriptively exploratory. Primary data were collected through interviews. The source of secondary data was mainly BPS and relevant worksheets. The analysis showed that the MYS and APK SM do well enough, while the APK-PT although above the achievements of the province is still below the national average. In the employment sector, white-collar entrepreneurial youth in Banjarbaru City is above the province and the nation. Youth Unemployment is above province, below the national. The problem in this sector is the mismatch between workforce competence and job opportunities. Abstrak Indeks Pembangunan Pemuda (IPP) merupakan suatu instrument untuk mengukur pembangunan kepemudaan di suatu wilayah. Pembangunan kepemudaan sangat penting dalam upaya menyiapkan sumber daya manusia yang berkualitas untuk melanjutkan pembangunan. IPP di Indonesia baru tersedia di tingkat provinsi, belum sampai ke tingkat kabupaten/kota. Meski demikian, kabupaten/kota juga berkewajiban untuk terus meningkatkan kualitas pembangunan kepemudaan dalam perencanaan pembangunan daerah untuk menunjang capaian IPP provinsi. Tulisan ini bertujuan untuk menganalisis pembangunan kepemudaan di sektor pendidikan dan lapangan & kesempatan kerja di Kota Banjarbaru berdasarkan indikator IPP di 2 domain tersebut, yaitu RLS, APK SM, APK PT, pemuda wirausaha kerah putih, dan TPT pemuda. Penelitian ini menggunakan pendekatan kualitatif dan dianalisis secara literatur review. Data primer diambil melalui wawancara, sedangkan data sekunder terutama berasal dari BPS dan dokumen kinerja SKPD yang relevan dengan objek penelitian. Hasil analisis menunjukkan bahwa domain Pendidikan sudah cukup baik, sedangkan di domain lapangan dan kesempatan kerja terdapat permasalahan TPT Pemuda yang cukup tinggi karena adanya ketidaksesuaian antara kompetensi tenaga kerja dengan lapangan pekerjaan yang tersedia.